RELATIONSHIP BETWEEN PHYSICAL ACTIVITY LEVELS AND PAINQUALITY IN PATIENTS WITHKNEE OSTEOARTHRITIS - Shalini A, Devadharshini J, Angeline R (Journal of Daoist Studies, 2026)
Background The impact of pain quality on physical activity in people with knee osteoarthritis (KOA) has been investigated in previous studies. Exercise enhances function, reduces pain, and decreases disability. Reduced physical activity is associated with pain, one of the main symptoms of KOA. This study evaluates how pain quality affects physical activity and focuses at clinical and sociodemographic correlations. Methods KOA patients (aged 40–70) were enrolled in a cross-sectional study from Sri Ramachandra Hospital's physiotherapy outpatient department. The Douleur Neuropathique4 (DN4) questionnaire was used to classify the subjects into neuropathic and nociceptive pain groups. Knee range of motion, hamstring and quadriceps strength, pain intensity, and demographic data were all collected. The Global Physical Activity Questionnaire (GPAQ) was used to measure physical activity. Results Among 111 participants, the neuropathic group (53) had higher pain severity (5.08 ± 1.06 vs. 4.72 ± 0.97, p < 0.05), reduced knee range of motion (98.77 ± 7.45 vs. 103.97 ± 6.93, p < 0.05), and lower physical activity levels (300.57 ± 198.83 vs. 504.14 ± 204.56 MET-min/week, p < 0.05). Physical activity correlated negatively with pain severity (r = -0.35, p <0.05) and pain quality (r = -0.41, p < 0.05) but positively with knee range (r = 0.29, p <0.05) and muscle strength (r = 0.32, p < 0.05). Conclusion: Compared to nociceptive pain, neuropathic pain in knee osteoarthritis is related to increased pain intensity, diminished physical function, and markedly decreased levels of physical activity. Enhancing physical activity levels and quality of life in this population requires targeted therapies that address both pain quality and functional limitations.